Implications of pregnant sheep nutrition on progeny\'s myofibers and blood parameters - Oliveira, Giuliana Micai de (2020)
The objective of the work was to evaluate the effect of different energy levels, as well as different energy sources in the diet of the ewes during pregnancy and its impact on growth and metabolism of lambs. Seventy-two ewes were used and randomly distributed in 5 different experimental treatments: diet (CTL) with 100% of the energy recommended by the NRC (2007), low energy (LE) diet with 90% of the recommended energy, or even high energy diets (HE) with 110% of the recommended energy level. HE diets were composed of three different energy sources: starch (ST), starch with chromium propionate (STCR) ou starch with fat protected (STFP). These diets were applied at the beginning and at the end of pregnancy, and during lactation. The impact of the plane of ewe nutrition on progeny, weight was evaluated from birth at 60 days, and blood samples were collected for biochemical parameters and blood count of these lambs (males and females) at 60 days of age in the first stage (infant stage) of the work. In the second stage (ruminant stage), male lambs were weaned at 90 ± 15 days and placed in a feedlot, where they remained for 60 days receiving the same diet. The lambs\' weight was evaluated every 14 days, and blood samples were collected for biochemical parameters and blood count before slaughter. After slaughter, carcass parameters and meat quality were evaluated. As a result of the infant stage, lambs from ewes diet HE, regardless of the source, were heavier and had greater weight gain (P < 0.05). Lambs from a single gestation stood out in terms of weight and weight gain (P < 0.05), as well as having a higher blood concentration of creatinine, protein, albumin and globulin than twin lambs, regardless of maternal nutrition (P < 0.05). Lambs from ST diet, stood out in terms of creatinine concentration (P < 0.05), which is used as an indicator of muscle mass accumulation. In the ruminant stage in feedlot, lambs from ewe diet ST and a twin pregnancy showed a higher concentration of glucose (P < 0.05), whereas those coming from the LE maternal diet showed a higher concentration of urea (P < 0.05). The initial and final weight in the feedlot, as well as the weight of the hot and cold carcass, were higher for lambs from STCR and STFP maternal diets and those from a single gestation (P < 0.05). The dressing was higher for lambs from CTL maternal diet (P < 0.05). With the exception of thaw losses, which was lower for lambs from LE diet, and cooking losses, which was higher for lambs from a ewe diet STFP (P < 0.05), no meat quality parameters were affected. The results show the impact of changes in nutrition during pregnancy and lactation, on production and physiological parameters associated with progeny health. Alternative sources of energy or supplements in a high energy maternal diet, such as chromium, have the potential to improve production.